A Servant to Many Masters: Competing Shareholder Preferences and Limits to Catering. (31st January 2014) - Manconi, Alberto; Massa, Massimo
Abstract: We study what determines catering through the payout policy and how catering affects firm value. We create a catering index, measuring how the firm caters to its investors' payout preferences. The index is based on the revealed payout preferences of mutual funds holding the firm's stocks. Catering is constrained by market segmentation and dispersion in investor payout preferences. It is also associated with positive value effects: Firms increasing their catering index also experience an increase in value. Furthermore, greater catering ability is associated with a more positive market reaction to corporate announcements of equity issues and dividend payouts.